ANTIOXIDANT ACTIVITY AND PHYSICOCHEMICAL PARAMETERS OF YOGURT ENRICHED WITH EXTRACTS OF RED HAWTHORN (CRATAEGUS MONOGYNA JACQ.) AND BLACK HAWTHORN (CRATAEGUS NIGRA WALDST & KIT.) - IRA TANEVA; ZLATIN ZLATEV (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The aim of this study was to determine some physicochemical parameters and antioxidant activity of fermented milks enriched with extracts of red hawthorn (Crataegus monogyna Jacq.) and black hawthorn (Crataegus nigra Waldst & Kit.) Antioxidant activity and the content of total phenols of water extracts of both species of hawthorn - red and black - were analyzed. The effect of the inclusion of the extracts in amounts of 5, 10 and 15 % of both species of hawthorn on the physicochemical and antioxidant properties of the obtained yogurts was monitored. Yogurts with the addition of red hawthorn extract (15 %) showed the highest phenolic content (TPC) and antioxidant properties determined by DPPH (2,2-Diphenyl-1-picrylhydrazyl) and FRAP (Ferric ion reducing antioxidant power) methods. Milk with extracts has better physicochemical properties (dry matter, syneresis and retention capacity). The use of hawthorn extracts in the production of yogurts is a new method for the development of dairy foods with functional properties.